Pemberdayaan Masyarakat Gampong Meunasah Blang Melalui Pengelolaan Sampah Rumah Tangga Berbasis Komunitas - Akhyar; Amiruddin; Usman; Marah Sutan Rangkuti; Hambali; Hartati; Muhammad Yusuf Zulkifli; Nur Asiah (STAI Nusantara Kota Banda Aceh, 2025)
The low level of public awareness regarding household waste management is a major concern in this community service activity. The impact of poor waste management includes a decline in environmental quality, increased risk of disease, and soil and water pollution. This community service activity aims to improve the knowledge and skills of the community in managing organic and inorganic waste through training and mentoring. The target community is Gampong Meunasah Blang, Ingin Jaya Sub-district, Aceh Besar District. The activity was implemented using a participatory approach, including education, demonstrations on processing organic waste into compost, and the formation of an independent waste management group. The results of the activity showed an increase in community understanding of waste management and the formation of an active waste management group. This activity has had a positive impact, improving the quality of the surrounding environment and fostering collective awareness among the community to maintain village cleanliness.